1989
DOI: 10.1128/mcb.9.7.3117
|View full text |Cite
|
Sign up to set email alerts
|

A double-stranded RNA-inducible fish gene homologous to the murine influenza virus resistance gene Mx.

Abstract: We cloned and sequenced a 2.35-kilobase EcoRI fragment of genomic DNA from a local freshwater fish (Perca fluviatilis) that strongly hybridized to probes derived from the murine influenza virus resistance gene Mx. The cloned fish DNA contained blocks of sequences related to Mx gene exons 3 to 8, which appeared to represent exons of a bona fide fish gene because they were separated by intron sequences flanked by consensus splice acceptor and donor sites. Injection of double-stranded RNA into the peritoneal cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…The crucian carp IRF-7 was induced within 1 h after IFN treatment and 12 h after ultravioletinactivate virus stimulation, suggesting that it is an early response molecule (Zhang et al, 2003). Fish Mx protein is expressed at a relatively late stage 18 h postpoly I: C stimulation (Staeheli et al, 1989), and its increased expression may last a few days (Jensen and Robertsen, 2000;Acosta et al, 2005). So the Mx protein is a relatively stable molecule compared with IRF-1 and IRF-7.…”
Section: Discussionmentioning
confidence: 99%
“…The crucian carp IRF-7 was induced within 1 h after IFN treatment and 12 h after ultravioletinactivate virus stimulation, suggesting that it is an early response molecule (Zhang et al, 2003). Fish Mx protein is expressed at a relatively late stage 18 h postpoly I: C stimulation (Staeheli et al, 1989), and its increased expression may last a few days (Jensen and Robertsen, 2000;Acosta et al, 2005). So the Mx protein is a relatively stable molecule compared with IRF-1 and IRF-7.…”
Section: Discussionmentioning
confidence: 99%
“…Mx proteins present a 70-80kDa GTPases of dynamin super family among vertebrates. The Mx gene in fish was first detected in 1989 15 and then seven forms of Mx genes were found in zebrafish 16 , three forms in rainbow trout 17 , two forms in crucian carp (Carassius auratus) 18 and a single form in Japanese flounder (Paralichthys olivaceus) 19 and Pufferfish 20 . However, the antiviral property of fish Mx proteins had been demonstrated only in Japanese flounder and Atlantic salmon against fish rhabdoviruses, infectious pancreatic necrosis virus, and viral haemorrhagic septicaemia virus 21,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The amino-acid residues identical to those of CaMx1 identified by the CLUSTAL W program (Thompson et al 1994) are indicated by asterisks; dashes indicate gaps introduced for optimal alignment. Ca Crucain carp, Dr zebrafish, Om rainbow trout, Ss Atlantic salmon, Hs human, Gg chicken system gene, Mx has been characterized from many fish species: seven copies for zebrafish (Lutfalla et al 2003), three copies for rainbow trout (Trobridge and Leong 1995;Trobridge et al 1997) and Atlantic salmon (Robertsen et al 1997); a single copy for perch (Staeheli et al 1989), Japanese flounder (Lee et al 2000), Atlantic halibut (Jensen and Robertsen 2000), gilthead sea bream (Tafalla et al 2004) and fugu (Yap et al 2003). The fugu Mx gene organization and regulatory region have also been characterized (Yap et al 2003).…”
mentioning
confidence: 99%